Work Stressors and Occupational Health of Young Employees: The Moderating Role of Work Adaptability - Zhou, Houyu; Zheng, Quangquang (Frontiers in Psychology, 2022)
Work adaptability serves as an individual's work experience, habits and skills that can adapt to current or changing working tasks and situations. It is a coping resource reserved by individuals to help them handle pressures. Based on Lazarus and others’ interaction model of work stressors, this study investigated 158 young employees from 20 organizations in Zhejiang province by means of interview research and questionnaire. The results show that the work adaptability of those young employees at their early career stage is between average and somewhat consistent levels, and the total score is slightly above average. Their work adaptability has a significant main effect on occupation health. The interaction of employees’ work adaptability exists between occupation health and lack of work meaning stress, role conflict stress, interpersonal relationship stress, unhealthy organization atmosphere stress, work stressor score, respectively. Young employees with high work adaptability tend to show worse occupation health under high-level stress due to lack of work meaning. To promote young workers’ occupation health, organizations should provide meaningful jobs or inform them of the significance of their jobs, reduce role conflicts, create a sound organizational atmosphere, etc. For the management, high-level stress due to lack of work meaning must be removed to retain young employees with high work adaptability. The findings provide insights into how work adaptability help young employee handle pressures and further improve occupational health. In the stress management of organization and self, continuous improvement of employees' work adaptability has positive significance and value for employees to effectively combat stress and maintain occupational health.